Neuropsychological and quality of life outcomes in PKU patients: expert recommendations of assessment tools in Brazil - Ida Vanessa Doederlein Schwartz; Andrea Amaro Quesada; Erlane Marques Ribeiro; Ana Maria Martins; Daniel Reda Fenga Vilela; André Pessoa (Arquivos de Neuro-Psiquiatria)
Background Phenylketonuria (PKU) is an inborn error of metabolism caused by deficient activity of phenylalanine hydroxylase. In Brazil, the National Neonatal Screening Program enables early treatment of patients with PKU, which prevents them from developing severe neurological damage and mental disabilities. However, between 20 and 30% of early-treated patients with PKU present focal cognitive deficits, including deficits in working memory, processing speed, and psychiatric symptoms such as anxiety, depression, and attention deficit hyperactivity disorder (ADHD). Therefore, age-specific neuropsychiatric and cognitive tests are important components of PKU patient care. To date, there are no officially approved guidelines or recommendations of tools in Portuguese validated for use in Brazil that could be applied to assess these parameters in patients with PKU.